A new record of the mudskipper Parapocryptes serperaster (Oxudercinae: Gobiidae) from Peninsular Malaysia - Khaironizam, M.Z.; Norma-Rashid, Y. (Malaysian Journal of Science, 2000)
One specimen of the mudskipper Parapocryptes serperaster (Valenciennes, 1837), a new record for Peninsular Malaysia, was captured at Sungai Sembilang, Jeram, Selangor. Its morphological features and habitat utilization are discussed. The preliminary feeding habit is described based on the gut contents